Radiotherapy of indolent orbital lymphomas - König, Laila; Hörner-Rieber, Juliane; Debus, Jürgen; Herfarth, Klaus (Strahlentherapie und Onkologie, 2016)
PurposeThe aim of this work was to retrospectively analyze efficacy, toxicity, and relapse rates of conventional (CRT) and low-dose radiotherapy (LDRT) in patients with indolent orbital lymphomas.Patients and methodsFrom 1987-2014, 45 patients (median age 64 years) with 52 lesions of indolent orbital lymphomas were treated with CRT (median dose 36 Gy, range 26-46 Gy) and 7 patients (median age 75 years) with 8 lesions were treated with LDRT (2 fractions of 2.0 Gy).ResultsMedian follow-up was 133 months (range 2-329 months) in the CRT group and 25 months (range 10-41 months) in the LDRT group. Overall response rates were 97.7 % (CRT) and 100 % (LDRT). The 2‑ and 5‑year local progression-free survival (PFS) rates were 93.5 and 88.6 %, distant PFS 95.0 and 89.9 %, and overall survival 100 and 85.6 % after CRT. In the LDRT group, 2‑year local PFS and overall survival remained 100 %, respectively, and distant PFS 68.6 %. Acute radiotherapy-related complications (grades 1-2) were detected in virtually all eyes treated with CRT. Cataracts developed in only patients who were irradiated with more than 34 Gy. LDRT was well tolerated with only mild acute and late complications.ConclusionPrimary radiotherapy of indolent orbital lymphomas is an effective treatment with high response rates and excellent local control in CRT and LDRT. In combination with close follow-up, LDRT may be an attractive alternative since re-irradiation even with conventional doses is still feasible.